New insights into the evolution and formation mechanism of SB5 fault: a case study from the Fuman Oilfield, Tarim basin, NW China - Song, Xingguo; Chen, Shi; Zhang, Yintao; Xie, Zhou; Neng, Yuan; Liang, Xinxin; Kang, Pengfei; Yang, Minghui; Chen, Ping (Frontiers in Earth Science, 2024)
The Shunbei 5 (SB5) strike-slip fault, situated in the central Tarim basin, is distinguished by its considerable length, significant variations in planar orientation, and intricate multi-stage tectonic evolution. This study delves into the geometric, kinematic, and dynamic features of both the southern and northern parts of the SB5 fault, utilizing the latest seismic data from the Fuman Oilfield, and examines the factors influencing the fault’s planar deflection. The fault can be categorized into three structural deformation layers based on lithological features and fault features: the deep structural deformation layer (below TЄ3), characterized by basement rifting and limited strike-slip activity; the middle structural deformation layer (TЄ3-TO3), marked by vigorous strike-slip movements and the dominance of flower structures; and the shallow structural deformation layer (TO3-TP), featuring echelon-type normal faults and boundary graben faults, specifically in the southern SB5 fault. The fault activity is more pronounced in its southern SB5 fault compared to the northern, with the weakest activity at the TЄ3 interface and the peak at the TO3 interface. The southern SB5 fault transitions to sinistral slip at the TO3 interface, while the northern SB5 fault shifts from dextral to sinistral slip at the TC interface, highlighting variable slip directions across different interfaces. Rifts are extensively distributed within the Precambrian basement along the SB5 fault. The initial strike-slip fault rupture, which is primarily localized in these areas, exerts a significant influence on the formation of the S-shaped fault plane. This process involves four distinct evolution stages: the embryonic stage of strike-slip activity during the Middle-Late Cambrian; the intense strike-slip fault activity stage during the Middle-Late Ordovician; the reactivation stage of deep strike-slip fault in the Silurian; and the connection and reactivation stage during the Devonian-Carboniferous.